Realidade psíquica e inconsciente em Freud e em Bérgson : considerações a partir de uma filosofia da ação - Cossu Junior, Franco (Universidade Federal de São Carlos, 2007)
Although both the Bergsonian philosophy and the Freudian metapsychology have been not properly considered, in the last decades, regarding an ample debate about the nature of the mind, it is about two recent speeches that might contribute significantly to the new theoretical-practical outlines in the contemporary philosophy and sciences that examine the mind. Both thoughts show the unconscious as something without what the psychic events could not be understood entirely, which demands total attention of any future scientific paradigm that intends to establish itself over the psychic phenomena. The key to this enterprise we find in the concept of Action, openly in Bergson, but also clearly in Freud who never withheld himself to understand the human in their constant relationship to the world around. It is not about the fusion of two speeches in the name of a new psychoanalysis , which inevitably might cause several epistemologic problems, but, chiefly, about the possibility to verify how much we can learn with the thesis about the mind that emerge from the both theories.
Keywords: Psicanálise; Filosofia; Inconsciente; Freud, Sigmund, 1856-1939; Bergson, Henri Louis, 1859-1941; Realidade psíquica; Metapsicologia; Corpo; Mental/Psychic reality; Unconscious; Body; Metapsychology; CIENCIAS HUMANAS::FILOSOFIA